Analysis of operational methane emissions from pressure relief valves from biogas storages of biogas plants. (October 2016) - Reinelt, Torsten; Liebetrau, Jan; Nelles, Michael
Highlights: Explosion-proof sensors can register triggering events from PRV. The used sensors provide the released methane emission and the duration of triggering. Methane emissions from PRV depend essentially on operational state. The emissions depend essentially on the availability of an automatic operated flare. Methane emissions from PRV also depend on atmospheric conditions. Abstract: The study presents the development of a method for the long term monitoring of methane emissions from pressure relief valves (PRV 1 ) of biogas storages, which has been verified during test series at two PRVs of two agricultural biogas plants located in Germany. The determined methane emission factors are 0.12 g CH4 kWhel −1 (0.06% CH4 -loss, within 106 days, 161 triggering events, winter season) from biogas plant A and 6.80/7.44 g CH4 kWhel −1 (3.60/3.88% CH4 -loss, within 66 days, 452 triggering events, summer season) from biogas plant B. Besides the operational state of the biogas plant (e.g. malfunction of the combined heat and power unit), the mode of operation of the biogas flare, which can be manually or automatically operated as well as the atmospheric conditions (e.g. drop of the atmospheric pressure) can also affect the biogas emission from PRVs.